Managing people : a competence approach to supervisory management - Collins, Michael; Green, George; Candy, Anita; Cartwright, Roger (Oxford : Blackwell Business, 1998)
This book provides a practical and accessible means of acquiring the knowledge and understanding essential to better performance in the workplace, and to the acquisition of vocational qualifications.
Keywords: Employees; Supervision; Supervision of employees